Pengaruh Model Pembelajaran Inkuiri Terhadap Motivasi Belajar PAK Bagi Siswa Kelas VIII SMP Negeri 1 Siempat Nempuh Hulu Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to determine the influence of the Inquiry Learning Model on PAK Learning Motivation for Class VIII Students of SMP Negeri 1 Siempat Nempuh Hulu for the 2023/2024 Academic Year. The method used in this research is a quantitative method with descriptive statistical data analysis. The population is all 165 students of class VIII of SMP Negeri 1 Siempat Nempuh Hulu for the 2023/2024 academic year who are Christians and the research sample was determined to be 47 people, namely 30% of the total population. Data was collected using a positive closed questionnaire with 52 items. The results of data analysis show that there is an influence of the Inquiry Learning Model on PAK Learning Motivation for Class VIII Students of SMP Negeri 1 Siempat Nempuh Hulu for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.546 > rtable( a=0.05,n=47) = 0.283, thus it is known that there is a positive relationship between variable -2=45)= 2.021, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 29.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=17, dk denominator=n-2=47-2=45) namely 19.09 > 1.51. Thus Ha is accepted and H0 is rejected.